Into the black nowhere ebook An unsub novel. - Gardiner, Meg (UNSUB, 2018)
From award-winning author Meg Gardiner, co-author of Michael Mann’s Heat 2 —In this exhilarating thriller inspired by real-life serial killer Ted Bundy, FBI profiler Caitlin Hendrix faces off against a charming, merciless serial killer. In southern Texas, on Saturday nights, women are disappearing. One vanishes from a movie theater. Another, from her car at a stoplight. A mother is ripped from her home while checking on her baby. Rookie FBI agent Caitlin Hendrix, newly assigned to the FBI's elite Behavioral Analysis Unit, fears that a serial killer is roaming the dark roads outside Austin. Caitlin's unit discovers the first victim's body in the woods, laid out in a bloodstained white baby-doll nightgown. A second victim in a white nightie lies deeper in the forest's darkness. Around the bodies, Polaroid photos are stuck in the earth like headstones, picturing other women with their wrists slashed. The women in the woods are not the killer's first victims, nor are they likely to be his last. To track the UNSUB, Caitlin must get inside his mind; he is a confident, meticulous killer, capable of charming his victims until their guard is down, snatching them in plain sight. He then plays out a twisted fantasy—turning them into dolls for him to possess, control, and ultimately destroy. Caitlin's profile leads the FBI to focus on one man: a charismatic, successful professional who easily gains people's trust. But can they apprehend him before it's too late? As Saturday night approaches, Caitlin and the FBI enter a desperate game of cat and mouse, racing to capture the cunning predator before he claims his next victim.